Social Intelligence and Self-Concept as Correlates of Marital Stability among Health Workers in Primary Health Care Facilities in Enugu State, Nigeria - Ugwu, Benedeth Lebechi; Anyanwu, Joy I.; Iwuagwu, Tochi Emmanuel; Nriamah, Deborah Chiebonam; Ozoeze, Gloria Anaezichi; Mamman, Jonah Chindo; Makinde, Veronica Ibitola (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Marital stability is the ideal expectation from every home globally. In contrary, instability of health workers in Enugu State is assuming an alarming rate. The study assessed social intelligence and self-concept as correlates of marital stability among health workers in Enugu State. A facility-based correlational study was conducted between December 2022 and March 2023 at various government primary care health facilities in Enugu State. A total number of 347 male and female health workers participated. Data collection was done using Social Intelligence Questionnaire (SIQ), Self Concept Questionnaire (SCQ), and Marital Stability Questionnaire (MSQ). The internal consistency reliability of the instruments was established using Cronbach’s alpha method. The reliability indices for SIQ, SCQ, and MSQ were .89, .80, and .78 respectively. Linear regression was used for analyses. The findings revealed that social intelligence (r = .328) and self-concept (r = .340) moderately correlate with marital stability among health workers in Enugu State. Social intelligence (β = .328, p < .001) and self-concept (β = .340, p < .001) are significantly correlated with marital stability among primary health care workers in Enugu State (p < .001). This research proves that increase in self-concept and social intelligence can help to increase and sustain marital stability. However, counsellors should organize workshops on social intelligence and marital stability to help health workers to achieve stable homes. Also, social welfare officers should organize self-concept intervention programmes for married couples to attain marital stablilty in their relationships.